(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Atoms of inert gases, helium, neon, argon, krypton, etc. under atmospheric pressure and temperature on earth exist freely as monatomic molecules indicating high degree of saturation of binding forces within such atoms. Apart from inert gas elements, atoms of all other elements under appropriate conditions of pressure and temperature tend to form polyatomic molecules in order that such atoms may gain identical electronic configuration existing in the inert gas elements.